Ideología y aculturación religiosa en una revista misionera del Perú del siglo xx - Plasencia Soto, Rommel (2021)
This article analyzes the main ideas from Misiones Dominicanas del Perú magazine, which publication began in 1919. Its text line (and that includes the photography profusely) shows us the conceptual and mental tools of a late evangelization process in the southern jungle of Perú. It also shows his determination to build with words and images a civilizing frontier in which the original subjects are absent.